A study of passive ventilation integrated with heat recovery - O'Connor, Dominic; Calautit, John Kaiser; Hughes, Ben Richard (Elsevier, 2014)
To meet the demand for energy demand reduction in heating, ventilation and air-conditioning systems, a novel design incorporating a heat recovery device into a wind tower was proposed. The integrated system uses a rotary thermal wheel for heat recovery at the base of the wind tower. A 1:10 scale prototype of the system was created and tested experimentally in a closed-loop subsonic wind tunnel to validate the Computational Fluid Dynamics (CFD) investigation. Wind towers have been shown to be capable of providing adequate ventilation in line with British Standards and the Chartered Institution of Building Services Engineers (CIBSE) guidelines. Despite the blockage of the rotary thermal wheel, ventilation rates were above recommendations. In a classroom with an occupancy density of 1.8 m2/person, the wind tower with rotary thermal wheel was experimentally shown to provide 9 L/s per person at an inlet air velocity of 3 m/s, 1 L/s per person higher than recommended ventilation rates. This is possible with a pressure drop across the heat exchanger of 4.33 Pa. In addition to sufficient ventilation, the heat in the exhaust airstreams was captured and transferred to the incoming airstream, raising the temperature 2 °C, this passive recovery has the potential to reduce demand on space heating systems.